Clonidine as an adjunct to intravenous regional anesthesia: A randomized, double-blind, placebo-controlled dose ranging study - Clarence S Ivie; Christopher M Viscomi; David C Adams; Alexander F Friend; Todd R Murphy; Colleen Parker (Wolters Kluwer Medknow Publications, 2011)
Background : The addition of clonidine to lidocaine intravenous regional anesthesia (IVRA) has been previously reported to improve postoperative analgesia in patients undergoing upper extremity surgery. Our objective was to perform a dose ranging study in order to determine the optimal dose of clonidine used with lidocaine in IVRA. Design & Setting : We performed a double-blinded randomized placebo-controlled study with 60 patients scheduled for elective endoscopic carpal tunnel release under IVRA with 50 ml lidocaine 0.5%. University-affiliated outpatient surgery center. Data collected in operating rooms, recovery room, and by telephone after discharge from surgery center. Materials & Methods : Sixty adult ASA I or II patients undergoing outpatient endoscopic carpal tunnel release under intravenous regional anesthesia.Patients were randomized into five study groups receiving different doses of clonidine in addition to 50 ml 0.5% lidocaine in their IVRA. Group A received 0 mcg/kg, group B 0.25 mcg/kg, group C 0.5 mcg/kg, group D 1.0 mcg/kg and group E 1.5 mcg/kg of clonidine.Intraoperative fentanyl, recovery room pain scores, time to first postsurgical analgesic, total number of acetaminophen/codeine tablets consumed postsurgery, incidence of sedation, hypotension and bradycardia. Results & Conclusions : There was no benefit from any dose of clonidine compared to placebo. There were no clonidine-related side effects seen within the dose range studied. In short duration minor hand surgery, the addition of clonidine to lidocaine-based intravenous regional anesthesia provides no measurable benefit.